Investigation of outlier detection algorithm - Šaltenis, Vydūnas (Lietuvos matematikos rinkinys, 2005)
The proposed outlier factor was used to analyze the multidimensional data sets regarding outlier detection. The paper describes two kinds of investigation: the influence of omitting some part of distances between data points, and the influence of additional (noisy) points to outlier detection quality. The results demonstrate the possibilities to improve the performance of computation and the stability of the outlier detection algorithm.